Sensitivity study of the planetary boundary layer and microphysical schemes to the initialization of convection over the Arabian Peninsula. (25th December 2019) - Schwitalla, Thomas; Branch, Oliver; Wulfmeyer, Volker
Abstract: In this study, we present a five‐member Weather Research and Forecasting (WRF) physics ensemble over the Arabian Peninsula on the convection‐permitting (CP) scale and investigate the ability to simulate convection and precipitation by varying the applied cloud microphysics and planetary boundary layer (PBL) parametrizations. The study covers a typical precipitation event ocurring during summertime over the eastern part of the United Arab Emirates (UAE). Our results show that the best results are obtained by using water‐ and ice‐friendly aerosols combined with aerosol‐aware Thompson cloud microphysics and the Mellor‐Yamada‐Nakanishi‐Niino (MYNN) PBL parametrization. The diurnal cycle of 2‐m temperature over the desert is well captured by all members, although a cold bias is present during the morning and evening transition. All members are capable of simulating the correct timing of the onset of convection. Simulations with the MYNN PBL and Thompson scheme produce the highest convective available potential energy (CAPE) and convective inhibition (CIN), associated with stronger mixing inside the PBL, leading to the formation of more dense liquid water clouds. The WDM6 microphysics scheme is not a suitable option, as there are hardly any liquid water clouds; mainly ice clouds are simulated. Precipitation is best captured by applying the MYNN and Thomspon scheme. Although the ensemble size is relatively small, this allows for the provision of cloud probability maps suitable for cloud‐seeding applications. Abstract : The prediction of cloud development and convergence zones in desert climates is a challenging task. Our high‐resolution simulations on the convection‐permitting scale are very useful tools to improve the simulation of clouds and thus precipitation. Our results indicate that an aerosol‐aware cloud microphysics scheme is most suitable for this purpose and ensemble simulations will provide uncertainties to improve cloud‐seeding guidance end efficiency.